Agronomic efficiency of liquid biofertilizers in potato cultivar Asterix - De Souza, Bruno Uehara; Oliveira, Roberta Camargos; Luz, José Magno Queiroz; Machado, Daniel Lucas Magalhães; Aguilar, Ariel Santivañez [UNESP] (My University, 2017)
The potato crop requires longer use of fertilizers, compared to all other cultures produced in Brazil. Therefore, it is important to conduct studies in, new sources that can enhance the balance between nutrients, improve soil's physical quality, provide nutrients based on the plant's needs and reduce environmental impacts. The objective this study was to evaluate the efficiency of liquid biofertilizer in potato, cultivar Asterix. The design was a randomized blocks, with four treatments and six replications. The treatments consisted in the application of biofertilizers Acorda + Aminosan + Fitofert; Fitofert; Acorda and a witness where there was no application of biofertilizer. Only for special class tuber yield, was difference between treatments, where the application of Acorda was more favorable, producing 39.83 t ha-1. When the three tested products applied, there is a negative effect on the productivity. Although the treatments did not differ in relation to soluble solids, all are within the ideal range, at the intermediate level, for use in industry.
Eficiência agronômica de fertilizantes organominerais líquidos em batateira, cultivar Asterix
Keywords: Fertilizer; Productivity; Solanum tuberosum; Soluble solids